A dinâmica das competências organizacionais: a trajetória do Grupo Paquetá - Froehlich, Cristiane (Universidade do Vale do Rio do Sinos)
The notion of competence should be understood under a dynamic perspective due to how fast changes take place in the competitive scenario. Considering the fact that changes are a constant factor in the market, dynamism is essential. In this scenario, the organization path can be considered as one of the key elements to understand the organizational dynamics, since this analysis presents a rich source of information and basis to understand the consolidation of organizational competences throughout time. The present work analyses the development of organizational competences in the different business of a shoes section of the State of Rio Grande do Sul (RS) and its articulation with the managerial practices, having as reference its history and the main changes that have happened. It is a qualitative research, with exploratory and descriptive characteristics, developed by the case study method in the Paquetá Group. The data were collected through semi-structured interviews and documental analysis. The main result
Keywords: estratégia; mudanças; trajetória da empresa; visão baseada em recursos; competência organizacional; change; resource-based view; strategy; organizational competence; Ciências Sociais Aplicadas